EFEKTIVITAS PENGEMBANGAN LEMBAR KERJA MAHASISWA PADA PERKULIAHAN BAHASA INGGRIS UNTUK MATEMATIKA - Cesaria, Anna; Fitri, Dewi Yuliana (STKIP PGRI Sumatera Barat, 2014)
Students' abilities can be developed through lectures,one of which is variable English for mathematics. In order for the maximum tuition required of a material that can support course lectures. In West Sumatra, Padang PGRI STKIP students only rely on one textbook only when the lectures, so the motivation and low student interest in learning. Therefore it takes a lecture materials that can help facilitate students in the lecture, which is a LKM. The purpose of this study is to develop a LKM valid, practical and effective in subjects STKIP PGRI English for mathematics in West Sumatra. This study is a research development. This LKM was developed by using the 4D model (define, design, develop, and desseminate). Phase desseminate not done. The data was collected with the validation and testing of the LKM. LKM is validated by the lecturer and expert English for mathematics, as well as Indonesian lecturers. Tests carried out on mathematics education students STKIP PGRI West Sumatra to know practicality and effectiveness of the LKM. The results showed that: LKM have been effective. This is evident from the activities of students and high motivation to learn after the lecture.